2005
DOI: 10.1103/physrevb.71.174307
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of slow atomic motion inSr8Ga16Ge30clathrate

Abstract: The clathrates feature large cages of silicon, germanium, or tin, with guest atoms in the cage centers. Sr 8 Ga 16 Ge 30 clathrate is interesting because of its thermoelectric efficiency, and its glasslike thermal conductivity at low temperatures, indicating Sr atom hopping within the cages. We measured 71 Ga NMR with a 9 T superconducting spectrometer down to 1.9 K. Knight shift and T 1 results are consistent with low density metallic behavior. The lineshapes exhibit changes consistent with motional narrowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 27 publications
4
36
1
Order By: Relevance
“…Recently, NMR and Mössbauer measurements have directly demonstrated atomic hopping within the cages of Sr 8 Ge 30 Ga 16 ͑Ref. 8͒ and Eu 8 Ge 30 Ga 16 , 9 respectively. The variety of electronic behavior attained by chemical substitution and doping suggests that significant new features may be produced in this system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NMR and Mössbauer measurements have directly demonstrated atomic hopping within the cages of Sr 8 Ge 30 Ga 16 ͑Ref. 8͒ and Eu 8 Ge 30 Ga 16 , 9 respectively. The variety of electronic behavior attained by chemical substitution and doping suggests that significant new features may be produced in this system.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6 Neutron diffraction measurements 6 revealed that the Ba atom in the large cage is located essentially at the center of the cage (6d site), whereas a substantial probability exists for the Sr atom to move off the site center about 0.3Å, to one of four crystallographically equivalent positions (24j or 24k sites), and Eu atoms move away even more, 0.4Å from the 6d site, suggesting that off-center rattling may be necessary to produce glass-like thermal conductivity . 13,14,15,16 At lower temperature, nuclear tunneling among the four sites 17,18,19 may also play the role. The on-center vibrational freedom of the Ba ions can be adequately described assuming independent harmonic oscillators (Einstein model), 6,13,20,21,22 but the Sr and Eu vibration cannot be satisfactorily modeled this way, indicating that anharmonic vibration contributions gain significance in these cases.…”
mentioning
confidence: 99%
“…NMR spin-lattice relaxation measurements were performed at the central transition frequency at the center of the lineshape. The relaxation time, T 1 , is a fitted value based on a magnetic relaxation mechanism using a standard multiexponential function for recovery of the central transition 15 . The quadrupole relaxation process entails a different relaxation function, which however leads only to an overall scaling of the T 1 , and does not affect any of the dynamical fitting parameters described below.…”
Section: Nmr Results and Discussionmentioning
confidence: 99%
“…The energy difference between the lowest two states, ∆E 12 ∼ = 30 K, is much smaller than those for higher energy levels, which agrees with recent reported results from other methods 13 , but with a larger ∆E 12 . This model can also be extended to a simplified 2-D potential by using r Compared to previous Ga NMR results for Sr 8 Ga 16 Ge 30 , also identified to behave as an anharmonic rattler system 2,16 , it seems initially surprising that the (T 1 T ) −1 in Sr 8 Ga 16 Ge 30 does not show a similar phonon-dominated behavior but instead follows a Korringa law quite closely for several decades of temperature 15 . However, a previous report for Sr-Ge clathrates used density functional theory to extract potential well parameters for Sr in the large cage 16 , giving a 2D anharmonic potential much like the model used here.…”
Section: Anharmonic Model and Fittingmentioning
confidence: 99%